Do Good Workplace Relationships Encourage Employee Whistle-Blowing?. Issue 4 (2nd October 2018) - Kyu Wang, Tae; Fu, Kai-Jo; Yang, Kaifeng
Abstract: The literature contains mixed arguments and evidence regarding how employee willingness to blow the whistle is affected by interpersonal relationships in organizations. This article examines whether there is a curvilinear relationship between interpersonal relationships and whistle-blowing intentions, by operationalizing interpersonal relationships with the person-group fit and person-supervisor fit variables. By using the 2015 Federal Employee Viewpoint Survey data, this article finds that the curvilinear relationship does exist: when the person-group fit and person-supervisor fit become very high, the intention to blow the whistle dwindles. As a result, this article argues that the impacts of workplace relationships on whistle-blowing intention would not be simply linear, but curvilinear.